Predictors of Financial Satisfaction: Mediating Role of Financial Behavior - Paudel, Sujan Raj; Ghising, Milan (Journal of Emerging Management Studies, 2024)
Purpose – The purpose of this paper is to examine the relationship between financial socialization, financial knowledge, and financial satisfaction with financial behavior as a mediator. Design/methodology/approach – The research used descriptive and causal-comparative research design. A questionnaire-based survey was used to collect data from 319 individuals living in the city of Lalitpur district of Kathmandu Valley, Nepal. To test the research hypotheses, the bootstrap re-sampling method was applied using Hayes’s SPSS multiple-mediator PROCESS macro. Findings – The results indicate that financial knowledge, attitude and management have a significant relationship with financial satisfaction. However, financial socialization has no significant relationship with financial satisfaction. The study also found financial behavior to play a mediating role in between predictors of financial satisfaction and financial satisfaction. Conclusion – Greater financial satisfaction is a result of having a positive attitude towards finances as well as having adequate financial knowledge and using efficient financial management techniques. The way that people manage their finances, budgeting, saving, and investing is a major factor in determining how satisfied they are with their overall financial situation. Implications - The insights from the paper suggest that tailored financial education programs and inclusive services can significantly enhance overall well-being. By leveraging personalized marketing and fostering open communication about money or wealth, stakeholders can empower individuals to make informed decisions and achieve greater financial security and satisfaction. Originality/value - This study stands out as one of the few studies to examine the relationship between predictors of financial satisfaction and financial satisfaction where financial behavior is a mediator.